(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY According to current evidence, one out of ten fracture patients with osteoporosis does not sustain another fracture if he or she is on adequate medication. However, epidemiological surveys show that only about 15 to 30% of affected patients avail themselves of the treatments. This cohort study investigated how many fracture patients with a recommendation for antiosteoporotic therapy effectively received treatment and the possible reasons why the treatment was not implemented. METHODS As part of a quality improvement programme in a Swiss trauma centre, fracture patients were actively checked for osteoporosis in accordance with a standardised outpatient programme. The results, together with detailed therapy recommendations, were transmitted to each patient’s general practitioner (GP). A prospective questionnaire survey evaluated all patients with a diagnosis of osteoporosis for subsequent realisation of therapy 1 year after the fracture (mean ± standard deviation; chi-square; analysis of variance; significance level p <0.05). RESULTS A total of 305 patients received a recommendation for antiosteoporotic therapy, of whom 18 (5.9%) died before 1 year. The questionnaire was completed for 255 out of 287 patients (follow-up 88.9%; 73.8±11.5 years old at the time of survey; 77.7% female). Of these, 117 patients (45.9%) sustained a fracture of the lower extremities and 105 patients (41.1%) a fracture of the upper extremities; 33 patients (13%) had other or multiple fractures. Fifty-two cases (20.4%) had pre-existing osteoporosis at the time of fracture. At the 1-year follow-up, 132 (52%) patients were receiving prescribed drugs. The most frequent patient explanation for not taking treatment (n = 123) was, in 47.2% of cases (n = 58), that none had been prescribed; 30.1% of patients were not interested. Multivariate analysis of verifiable factors of influence confirmed that fracture patients were treated significantly more reliably with antiosteoporotic therapy if osteoporosis was diagnosed with dual energy x-ray absorptiometry alone in patients with fewer comorbidities, and that fracture patients persisted significantly more reliably with antiosteoporotic therapies when pre-existing osteoporosis was present (R2 0.17; p <0.001). CONCLUSIONS Following a standardised diagnostic work up for osteoporosis as part of fracture treatment, and including the communication of recommendations for antiosteoporotic therapy to the GP, only every second patient actually received the proposed treatment. This appears to be better than described in the literature but still calls for improvement. Two different solutions appear to be possible based on these findings: to endeavour to better inform and convince GPs about the need for treatment and/or for the diagnosing team to initiate antiosteoporotic therapy where indicated rather than just recommending it.